Fotografi Dokumenter “Surabi” melalui Metode EDFAT1 - Shauma Silmi Faza (PANTUN, 2019)
The method applied in the producing of this documentary photography is EDFAT: Entire, Detail, Frame, Angle, Time. EDFAT is a method which is still rarely used among academicians but usually applied by professionals especially journalists or photographers. This study is creative process to understand and apply EDFAT method. The object of this study is Surabi sellers in Bandung city, they are, Surabi Ema Ayu, Surabi Cihapit, and Waroeng Setiabudhi. The result of the study depicts the phenomena of the changes of Surabi in Bandung City from traditional such as Surabi Ema Ayu, to modern such as Surabi Cihapit and Waroeng Setiabudhi. Keywords: Documentary Photography, Traditional Surabi, Modern Surabi, EDFAT